Violent Sexual Homicide: An Unusual Case Report - Sethi, Abarnita; Dash, Braja Kishore; Jena , Manoj Kumar (Journal of Indian Academy of Forensic Medicine, 2015)
Violent crimes against women with sexual overtones have always been perpetuated despite  being considered one of the lowliest of acts. Recently there is an upsurge seen in these types of  inhuman instances. This reflects an abnormal feudal psychosocial behavior, the underlying reasons being  many and not completely explained. We present a case of sexual homicide where an unclothed female  body was recovered from a river. Autopsy conducted the next day revealed a young female body with  multiple injuries all over the body including bite marks, gross genital mutilation and fatal cranio- cerebral  injuries. The alleged accused examined the day after showed numerous scratch abrasions on his body.  We intent to discuss the psychosocial and behavioral problems arising out of illicit sexual relationship and  hope it serves as a warning to the society of its possible fatal outcome. Finally the Forensic pathologist  should do their duty meticulously to preserve every piece of evidence and give a scientific opinion to help  the law to carry out justice against such monstrous act.
Keywords: Sexual assault; Homicide; bite marks; Genital mutilation